Lipid profile of type 2 diabetics in Almajmaah, Saudi Arabia - Sami, W.; M. R., Abdul Hamid (IOP Publishing, 2019)
This research evaluated the lipid profile of type 2 diabetics in Almajmaah, Saudi Arabia. There is scarcity of literature about the assessment of lipid profile of type 2 diabetics in Saudi Arabia with very few studies addressing this issue. The data was collected from 350 diabetic patients visiting the primary healthcare centres in Almajmaah, Saudi Arabia. The questionnaire comprised of socio-demographic and clinical data information. Systematic random sampling technique was used to collect the data from available sample frame of type 2 diabetics. The median age of the patients was 45 (40 – 51) years. Majority of the patients were males as compared to females (57.7% vs 42.3%). A significant dyslipidaemia was observed in diabetics. Patients had significantly high LDL, and TG level (p < 0.001) respectively. HDL-C of males was significantly high, whereas, for females, it was at borderline (p < 0.001) respectively. However, TC was not statistically significant (p = 0.405). The prime focus when treating diabetics is to introduce preventive and therapeutic lifestyle changes measures into a comprehensive treatment programme. The treating doctor must keep an eye on the lipid profile of diabetics that can be useful for the patients to reduce the morbidity from macrovascular complications.